Comprehensive molecular expression profiling of SARS-CoV-associated factors in the endometrium across the menstrual cycle and elevated susceptibility in women with recurrent pregnancy loss - Qi, Ruofan; Guan, Rui; Cai, Shengyun; Xu, Mingjuan; Yang, Wen-jui; Wang, Chi Chiu (Frontiers in Genetics, 2023)
Objective: To evaluate the dynamic expression profiling alterations of SARS-CoV-2associated molecules within the fertile human endometrium throughout the menstrual cycle. Furthermore, to explore the inherent vulnerability of the endometrium to SARS-CoV-2 infection among women experiencing recurrent pregnancy failures, including both recurrent implantation failures (RIF) and recurrent pregnancy losses (RPL).The present study employed multiple datasets to investigate the expression patterns of SARS-CoV-2-associated genes. Firstly, a single-cell RNA-sequencing dataset comprising endometrial samples from 19 healthy women across the menstrual cycle was utilized. Additionally, two microarray datasets encompassing 24 women with RIF, and 24 women with RPL during the peri-implantation phase were included. To complement these analyses, immunohistochemical (IHC) staining was performed on endometrial samples collected from 30 women with RIF, 30 women with RPL, and 20 fertile controls recruited specifically during the implantation period.The investigation revealed a moderate expression percentage of CTSL (22%), TMPRSS4 (15%), FURIN (16%) and MX1 (9%) in endometrium. Conversely, the expression percentages of ACE2 (1%) and TMPRSS2 (4%) were relatively low.2 Notably, the expression of BSG exhibited an increment towards the window of implantation, reaching its peak during the middle secretary phase. Furthermore, a significant reduction (P<0.05) in TMPRSS2 expression was observed in the RIF group compared to the control group. While the expression of BSG was significantly increased (P<0.05) in the RPL group, findings that were corroborated by the IHC staining results.The findings of this study indicate a noteworthy upregulation of BSG expression in the endometrium of women with RPL. These results suggest an augmented susceptibility of endometrium to SARS-CoV-2 infection, potentially contributing to unfavorable pregnancy outcomes.